Biomechanical comparison of a modified TPLO plate, a locking compression plate, and plate-rod constructs applied medially in a proximal gap model in canine synthetic tibias - G. Sembenelli; G.V. Souza; M.C.N. Wittmaack; A.C. Shimano; T.A.S.S. Rocha; P.C. Moraes; B.W. Minto; L.G.G.G. Dias (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2022)
ABSTRACT The aim of this study was to develop a modified tibial plateau leveling osteotomy (TPLO) plate and to compare its biomechanical properties with a locking compression plate (LCP) and plate-rod constructs for the stabilization of experimentally induced gap fractures in canine synthetic tibias. The tibial models were assigned to either repair with a modified TPLO plate (Group 1), locking compression plate construct (Group 2), or plate-rod construct (Group 3). The specimens were loaded to failure in axial compression, three-point mediolateral and craniocaudal bending. There was no statistical difference between the three groups regarding stiffness (N/mm) and deformation (mm) in axial compression. The modified TPLO plate achieved load to failure similar to the plate-rod construct in craniocaudal bending. There was no significant difference between groups on mediolateral bending tests regarding load to failure and deformation. Furthermore, there was no significant difference in stiffness between groups 1 and 2. In conclusion, the modified TPLO plate had similar mechanical properties to LCP and plate-rod construct in the axial compression and bending tests. Nonetheless, clinical studies with a large population of dogs are required to determine the value of this new implant in proximal tibial fracture repair.